A study on mechanisms of imipenem resistance in burkholderia pseudomallei BUPS01/14 - Zamani, Afiqah (2018)
Background: Recently, there is an increasing trend of online health seeking behavior in Malaysia and at global level. In addition, social media platforms are gaining recognition as a new communication channel for public health organizations due to its ability to disseminate information faster and wider reach. Yet, little are known on factors associated to netizens engagement on the social media platforms in Malaysia. Objective: This study aims to determine type of health information, type of post and time of post conveyed on Ministry of Health (MOH) Malaysia’s Facebook (FB) Page between November 2016 to October 2017 and its engagement rate. This study also to determine association between type of post and time of post with type of health information as well as factors associated between type of health information, type of post and time of post on good engagement rate among netizens. Methodology: This study applied a cross-sectional design with secondary data gathered from Facebook Insight of MOH’s FB Page from 1st November 2016 to 31st October 2017. The study was conducted from 1st January until 30th April 2018. All 2123 randomly selected posts were analyzed using logistic regression model to identify factors associated with good engagement rate.Results: In our analysis, the most prevalence type of health information is organizational promotion whereas most time of posted was noted during early morning (0000H – 0759H) and the most type of post was photo. Majority of posts in this study were considered as poor or average engagement rate. There was significant association between type of health information and media richness (p<0.001). Yet, no association was found between type of health information and time of post. Besides, good engagement rate was associated with health education (OR: 3.80, p<0.001), risk communication post (OR: 1.77, p<0.001), afternoon (OR: 1.76, p<0.001), evening post (OR; 1.48, p<0.001) and video post (OR; 3.74, p=0.007) after few variables were adjusted. In addition, posting a FB post on morning period, using link, shared video or photo showed negative associations with engagement rate among netizens on MOH FB Page. Conclusion; Results highlight the factors associated with health information engagement among netizens on MOH FB Page. Health education, risk communication, evening post and video post have shown significant associations with good engagement rate. These data suggested a comprehensive and strategic health communication approaches on social media may improve the engagement on the health contents provided by public health organizations to public.